THE GUARDIAN OR THE GRANTOR: THE ROLE OF NARCISSISTIC PERSONALITY AND MORAL REASONING IN AUDIT RISK - Nabiilah Putri; Diendha Annisa Nur Attaullah; Yusnaini Yusnaini (PT. Media Akademik Publisher, 2026)
Auditors play a crucial role as